The Influence of Product Quality and Promotional Activities on Consumer Purchase Intention on the TikTok Shop Platform - Santy Devipel Nainggolan; Maria Assumpta Wikantari (Publikasi Indonesia, 2026)
This research explores the impact of product quality and promotional strategies on consumer purchase intention within the TikTok Shop ecosystem. Employing a quantitative framework, the study gathered data through consumer surveys, which were subsequently analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings demonstrate that product quality serves as a primary driver of purchase intention, showing a strong and significant positive effect. Similarly, promotional activities were found to play a crucial role in significantly boosting consumer interest. Beyond individual effects, the simultaneous analysis confirms that both variables collectively enhance the likelihood of consumer engagement. These results suggest that in the social commerce landscape, the combination of superior product standards and interactive marketing is essential for capturing the market. Consequently, digital entrepreneurs are encouraged to harmonize high-quality offerings with dynamic promotional tactics to solidify their competitive advantage and drive purchasing decisions on the platform. Strategic integration ensures business growth.